Program Planning Theory in Service-Learning: A Relational Model - Robin S. Grenier; Lorilee R. Sandmann; Richard Kiely (Adult Education Research Conference, 2008)
This paper introduces the relationship between program planning theory and service-learning in graduate education and the development of a relational program planning model for service-learning. A case will be made regarding the value of the relational program planning model for guiding and enabling more democratic forms of service-learning practice.
Keywords: service-learning; program planning; adult education